Testing Effect Mediation of Regional Expenditure on Gross Regional Domestic Products - Armawaddin, Muhamad; Nur, Syamsir (Faculty of Economics and Business, University of Muhammadiyah Malang, 2018)
This study aims to analyses and determine the dominant factors that influence regional spending and its impact on gross regional domestic products and to analyses the direct and indirect effects of regional own revenue, general allocation fund and revenue sharing fund on gross regional domestic products mediated by regional expenditure. Data uses panel data with 17 Regency / Municipality in Southeast Sulawesi and observation period for 2015-2017. Data analysis used path analysis with AMOS 18.0 program and indirect effect test using the Sobel test. The results of the study conclude: a) General Allocation Funds and Revenue Sharing Funds significantly affect Regional Expenditures, while Regional Own Revenues are insignificant; b) Regional Own Revenue and Revenue Sharing Fund significantly affect the Gross Regional Domestic Product, while the General Allocation Fund is not significant; c) Regional Expenditure significantly mediated the effect of General Allocation Funds and Revenue Sharing Fund on Gross Regional Domestic Products, while Regional Expenditures do not significantly mediate in the influence of Regional Own Revenue on Gross Regional Domestic Product. Whereas to increase the gross regional domestic products in Regency / Municipality in Southeast Sulawesi, it is better to regulate Regional Expenditure allocations sourced from the General Allocation Fund.